Hungarian Monitoring, 5 May 1988 . [Magyar rádiófigyelő], 1988. május 5 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Party assembly in Belgrade - Polish strikes, arrests - Pravda article on nationalism - Soviet photojournalist shot in Afghanistan - Israeli troops withdraw from Southern Lebanon Domestic Affairs: - Károly Grósz's schedule in London - Hungarian-Japanese parliamentary talks - Freedom of opinion and point of view in the Party: debate forum in the Political College - Training for environmental professionals - György Győrffy awarded Herder Prize Economy: - Difficult situation facing artisans - Changing consumer prices Külpolitika: - Pártértekezlet Belgrádban - Lengyel sztrájkhelyzet, letartóztatások - Pravda cikk a nacionalizmusról - Afganisztánban lelőttek egy szovjet fotóriportert - Izraeli csapatok visszavonása Dél-Libanonból Belpolitika: - Grósz Károly londoni programja - Magyar-japán parlamenti megbeszélések - A párton belüli vélemény és nézetszabadság:vitafórum a Politikai Főiskolán - Környezetvédő szakember képzés - Győrffy György Herder-díjat kapott Gazdaság: - Kisiparosok nehéz helyzetben - Fogyasztói árváltozások